Healthcare Personnel and Middle East Respiratory Syndrome Coronavirus: A systematic review - Ameera Khaled Mansour Alghamdi; Ibrahim Mohammed Hamed Alhassani; Hossam Mohammad H Alnaji; Mohammad Saeed M Algarni; Abdullah Jaber Nasser Alsallum; Abdulrahman Abdullah Mohammed Bani Humayyim; Bandar Fahad Mana Al Shuqayh; Ali Raja Sulaiman Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: coronavirus (MERS-CoV) is transmitted to healthcare workers in the Middle East at high rates and with high morbidity and mortality. Methods: we performed a thorough and systematic search across multiple databases, such as PubMed, Web of Science, Embase, and Scopus. This review incorporates a total of 17 studies that were selected for an in-depth examination and description. Findings: Out of 152 articles on Coronaviruses, 17 papers consider MERS-CoV transmission to healthcare workers. Of these, most originate from Saudi Arabia, where there is a considerably higher incidence of MERS-CoV compared to other countries in the region. The main source of human infection is through contact with contaminated dromedary camels. Conclusion: The attainment of strong results for the implementation of strict infection control measures is of utmost critical importance. Sticking to respiratory hygiene practices, hand hygiene, and cough etiquette by all individuals showing symptoms of respiratory infections can achieve a marked decline in the infection rate among healthcare workers. It is equally important that supplies for hand hygiene are adequately available at all times to every healthcare worker.